Implementasi Strategi Marketing Mix 4P dan Konsep Technopreneurship pada Produk Air Minum dalam Kemasan (AMDK) Internal Kampus - Rifqi Firmansyah; Hani Humaeriyah (INDO PUBLISHING, 2026)
The growth of creative business units within the academic environment has become a crucial pillar in supporting the vision of a technopreneurship-based university. This study aims to analyze the implementation of the 4P marketing mix strategy and the technopreneurship concept for the LUMINE bottled water (AMDK) product at Universitas Muhammadiyah Bandung. The research method used is descriptive qualitative, with data collection techniques including questionnaires distributed to 20 student respondents and a needs assessment survey for campus work units/institutions. The results show that LUMINE has a stable institutional market absorption potential, with an average requirement of 20 gallons per week and 50 boxes of 330ml bottles per month from the household unit. Individual market validation indicates an 85% student buying interest driven by campus identity factors, while 95% of respondents prioritize hygiene (BPOM/Halal certification). The implementation of technopreneurship is carried out through a contract manufacturing (makloon) system, which provides operational efficiency by minimizing investment in physical infrastructure. The study's conclusion confirms that LUMINE is marketingly and operationally feasible as an innovative flagship campus product.